Style and Otherness in L.-F. Céline's Rigodon - Ann L. Murphy (Studies in 20th & 21st Century Literature, 1994)
L.-F. Céline's preoccupation with the question of style appears not only in his correspondence, interviews and "socio-political" (i.e. anti-Semitic) tracts, but also in his novels. An examination of Céline's thoughts on the writing of, and in, novels reveals an opposition between features which should inform style, and those which should be eliminated, in other words, between those values upon which his own style rests, and those associated with non-style, with his "others of style." Two passages in his final novel Rigodon may be read as figuring certain aspects of these thoughts as well as some of the paradoxes which accompany them. The first passage is the description of character Horace Restif's assassination method which, although its features correspond to Céline's opposition to otherness in the form of reason and ideas, exposes the complicity between his style and illusion and artifice, the "unauthentic" against which he rails in his pamphlets and elsewhere. The second passage figures Céline's conception of style as revelation, as a journey to the inside of spoken language in order to uncover its secret relationship to emotion. However, while the journey inward is rewarded with discovery, the correlative journey outward is one toward meaning, communication, and the textual, various components of the otherness that distances the individual from his lived experience.
Keywords: Louis-Ferdinand Céline; style; correspondence; interviews; socio-political; anti-Semitic; novels; tracts; inform; features; non-style; others of style; Rigodon; paradoxes; Horace Restif; character; assassination method; opposition to otherness; other; reason; illusion; artifice; unauthentic; pamphlets; revelation; journey; journey inward; journey outward; meaning; communication; textual; otherness; distance; distances; self; individual; lived experience